(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
The development of entrepreneurship among high school (SMA) students is a strategic effort to create an independent and innovative young generation. This article discusses the community service program implemented at Baranglompo’ High School to improve students’ entrepreneurial skills through business simulation methods. This program is designed to provide students with practical experience in managing a small business, from planning to operational implementation. The method used is training and direct practice in the form of a business simulation, where students act as entrepreneurs who manage their businesses. This program involves activities such as business planning, marketing, financial management, and performance evaluation. The results of the service show a significant increase in students’ understanding of the concept of entrepreneurship and their ability to apply business theory to real practice. Additionally, students also show improvements in management, decision-making, and teamwork skills. This program successfully fosters an entrepreneurial spirit among students, prepares them for the challenges of the business world, and provides valuable practical experience. This program concludes that business simulation is an effective method for developing entrepreneurial skills among high school students. This program not only increases students’ knowledge and skills but also motivates students to become creative and innovative young entrepreneurs. Thus, developing entrepreneurship through business simulations can be one solution to facing economic challenges in the future, especially in creating new jobs and reducing unemployment rates among youth. — Pengembangan kewirausahaan di kalangan siswa sekolah menengah atas (SMA) merupakan upaya strategis untuk menciptakan generasi muda yang mandiri dan inovatif. Artikel ini membahas program pengabdian masyarakat yang dilaksanakan di SMA Baranglompo’ dengan tujuan untuk meningkatkan keterampilan kewirausahaan siswa melalui metode simulasi bisnis. Program ini dirancang untuk memberikan pengalaman praktis kepada siswa dalam mengelola bisnis kecil, mulai dari perencanaan hingga pelaksanaan operasional. Metode yang digunakan adalah pelatihan dan praktik langsung dalam bentuk simulasi bisnis, di mana siswa berperan sebagai pengusaha yang mengelola usaha siswa sendiri. Program ini melibatkan kegiatan seperti perencanaan bisnis, pemasaran, manajemen keuangan, dan evaluasi kinerja. Hasil pengabdian menunjukkan peningkatan signifikan dalam pemahaman siswa terhadap konsep kewirausahaan dan kemampuan siswa dalam menerapkan teori bisnis ke dalam praktik nyata. Selain itu, siswa juga menunjukkan peningkatan dalam keterampilan manajemen, pengambilan keputusan, dan kerja sama tim. Program ini berhasil menumbuhkan semangat kewirausahaan di kalangan siswa, mempersiapkan siswa untuk tantangan dunia bisnis, dan memberikan pengalaman praktis yang berharga. Kesimpulan dari program ini adalah bahwa simulasi bisnis merupakan metode yang efektif dalam pengembangan keterampilan kewirausahaan di kalangan siswa SMA. Program ini tidak hanya meningkatkan pengetahuan dan keterampilan siswa, tetapi juga memotivasi siswa untuk menjadi pengusaha muda yang kreatif dan inovatif. Dengan demikian, pengembangan kewirausahaan melalui simulasi bisnis dapat menjadi salah satu solusi dalam menghadapi tantangan ekonomi di masa depan, khususnya dalam menciptakan lapangan kerja baru dan mengurangi angka pengangguran di kalangan pemuda.